(untitled) (Communication & Society, 2013)
Public diplomacy is an international political communication activity to which States and other organizations resort in order to achieve political objectives abroad and to establish positive relations with foreign publics. It is an activity that has evolved to adapt to the new global context, adding new characteristics and giving place to the so-called “new public diplomacy”. One of the different variants of public diplomacy is mediatic diplomacy, whose end is to get the public diplomacy’s message transmitted by institutional media or to get a positive coverage by foreign media. This article proposes a specific process to apply the framing theory as a tool for political discourse analysis, an essential element of mediatic diplomacy. The process is applied to George W. Bush’s political discourse during the first months of the “War on Terror”.